2022
DOI: 10.1186/s12955-022-01917-x
|View full text |Cite
|
Sign up to set email alerts
|

Rural population’s preferences matter: a value set for the EQ-5D-3L health states for China’s rural population

Abstract: Purpose To develop an EQ-5D-3L social value set based on Chinese rural population’s preferences using the time trade-off (TTO) method, and to compare the differences in preferences on health states between China urban and rural population. Methods Between Sep 2013 and Nov 2013, a total of 1201 participants were recruited from rural areas of five Chinese cities (Beijing, Chengdu, Guiyang, Nanjing, and Shenyang) using a quota sampling method. Each re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This discrepancy may arise from several factors: firstly, our study focused on the middle-aged and elderly in rural northwest China, exhibiting cultural differences and distinct perspectives on health issues compared to other studied populations. Secondly, the EQ-5D-3L health state utility values we utilized were tailored to the preferences of the rural Chinese population in 2022 ( Liu et al, 2022 ). Lastly, our research results indicate that pain/discomfort is the most commonly reported issue by respondents, consistent with other studies ( Huang et al, 2017 , Yao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy may arise from several factors: firstly, our study focused on the middle-aged and elderly in rural northwest China, exhibiting cultural differences and distinct perspectives on health issues compared to other studied populations. Secondly, the EQ-5D-3L health state utility values we utilized were tailored to the preferences of the rural Chinese population in 2022 ( Liu et al, 2022 ). Lastly, our research results indicate that pain/discomfort is the most commonly reported issue by respondents, consistent with other studies ( Huang et al, 2017 , Yao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…( Chen et al, 2020 ). The EQ-5D-3L health utility value formula based on the preference setting of Chinese rural population was used for calculation ( Liu et al, 2022 ). Utility value = 1–0.053–0.100*MO2 − 0.261*MO3 − 0.104*SC2- 0.224*SC3 − 0.080*UA2 − 0.206*UA3 − 0.101*PD2 − 0.234*PD3 − 0.080*AD2 − 0.189*AD3 − 0.019*N3.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the absolute utility score could also influence the QALY calculation to some extent. Hence, more empirical studies are warranted to further assess the impact in various settings in China.We also acknowledge a new 3L value set for China’s rural population developed by Liu et al has been available recently [ 38 ]. They also found that the utilty scores generated from the value set were generally lower than those of the two 3L value sets used in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These responses were subsequently converted into a single index value ranging from 0 (death) to 1 (full health) using the specific Chinese value set. 22 , 23 An index value <0 was classified as a bad health status worse than death.…”
Section: Methodsmentioning
confidence: 99%